2017
DOI: 10.1002/maco.201709476
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion studies on Fe‐30Mn‐1C alloy in chloride‐containing solutions with view to biomedical application

Abstract: Austenitic Fe‐30Mn‐1C (FeMnC) is a prospective biodegradable implant material combining high mechanical integrity with adequate corrosion rates. The fast solidified TWIP alloy, its constituents and 316L stainless steel were electrochemically analysed in various electrolytes at 37 °C under laminar flow. Potentiodynamic polarization tests were conducted in Tris‐buffered simulated body fluid (SBF), in Tris‐buffered saline (TBS) and in 150–0.15 mM NaCl solutions (pH 7.6, 10, 5, 2) to study initial corrosion stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…TWIP steels have excellent strength and ductility. The studies confirmed that TWIP (Fe-Mn-C) alloys degrade in a physiological environment [134][135][136][137].…”
Section: Iron-manganese Alloyssupporting
confidence: 64%
“…TWIP steels have excellent strength and ductility. The studies confirmed that TWIP (Fe-Mn-C) alloys degrade in a physiological environment [134][135][136][137].…”
Section: Iron-manganese Alloyssupporting
confidence: 64%
“…In Figure 6b, a SEM image of a FeMnCS (SLM) sample surface after 7 days of static immersion in SBF is shown with a relatively homogenous layer of corrosion products. According to EDX studies (Figure 6c-f ), by revealing a high concentration of Ca, P, and O in the layer as well as to previous X-ray photoelectron spectroscopy (XPS) studies of cast Fe-30Mn-1C-0.025S surfaces [11,42] and further investigations of FeMn-based alloys immersed in pseudo-physiological solutions, [8,10] the formation of hydroxyapatite can be assumed. Also, salt precipitations and the formation of oxides are quite probable.…”
Section: Corrosion Testing Of Bulk Samples In Sbfsupporting
confidence: 60%
“…[7,10,11,42] In contrast to SLM-processed FeMnCS, the cast dual-phase FeMnCS alloy shows a combination of uniform and localized corrosion, leading to a stronger corrosive attack, whereby the analysis of the fundamental corrosion process was presented in previous studies. [11,42] This can be attributed to the enrichment of the most reactive Mn and depletion of Fe along the austenite grain boundaries, which promote the corrosion attack along these areas. Furthermore, finely distributed manganese sulfide precipitates in the cast modification ( Figure 2d) dissolve preferentially in SBF and are initiation sites for pitting corrosion.…”
Section: Corrosion Testing Of Bulk Samples In Sbfmentioning
confidence: 99%
“…Moreover, Dargusch, Dehghan-Manshadi, Shahbazi, Venezuela, Tran, Song, Liu, Xu, Ye and Wen [ 17 ] claimed that the corrosion rates of Fe–Mn alloys increased with increments in Mn content while the corrosion rates derived from potentiodynamic curves were consistent with those obtained from the immersion tests. They also pointed out that while the presence of Fe and Mn oxides post degradation had been consistent across various studies [ 11 , 12 , 14 , [17] , [18] , [19] , [20] , [21] , [22] , [23] ], the presence of Fe/Mn phosphates, has not been consistently observed despite the mention of phosphorus among detected elements in corrosion products [ 5 , 14 ]. The state-of-art on the degradation of Fe–Mn alloys reviewed here clearly highlights that there is a lacuna of knowledge in the field.…”
Section: Introductionmentioning
confidence: 72%
“…The exact effect of such inclusions on the degradation rate of FeMn-based alloys has not yet been investigated, however Hermawan et al [ 19 ] suggested their potential at triggering micro-galvanic corrosion by providing microsites with different potential than the base metal. Besides these aspects, elemental segregation at grain, or particle boundaries, has been shown to have positive effects on corrosion acceleration for both powder-processed Fe30Mn microstructures [ 39 ] as well as induction melted Fe30Mn1C [ 18 ]. Similarly, tuning the grain sizes also has a marked effect on the degradation rate of both powder-processed [ 29 ] and wrought [ 40 ] Fe-based materials.…”
Section: Introductionmentioning
confidence: 99%